Tantangan Belajar di Tengah Pandemi COVID-19 - Udur Silaban; Roma Purba; Cut Kumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
During the COVID-19 pandemic, the implementation of teaching and learning activities underwent significant changes. Schools that usually conducted face-to face learning had to switch to online learning. However, online learning did not always run smoothly; many challenges emerged, particularly in terms of access to technology such as mobile phones, laptops, and stable internet connections. In addition, not all parents were able to accompany their children in learning from home due to busy schedules or limited knowledge. This situation made it difficult for students to understand the material delivered by teachers online. The home learning environment was also very different often unconducive and lacking direct interaction which led many students to feel confused and unmotivated. These challenges made the learning process during the pandemic less effective and required all parties to find solutions so that education could continue to run well, even when conducted online.